Efektivitas Pelayanan Pengambilan Sampah oleh Bumdesma Lekok Asri di Wilayah Pesisir Desa Wates - Ariska, Siti Nurul; Rossa Ilma Silfiah (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the effectiveness of waste collection services provided by the Lekok Asri Village-Owned Enterprise (BUMDesma) in the coastal area of Wates Village, Lekok District, Pasuruan Regency. The research method used was descriptive qualitative, with data collected through in-depth interviews, direct observation, and document study. Data were analyzed using the interactive model of Miles, Huberman, and Saldana. The results indicate that waste collection services are generally well-organized and cover the entire area. However, their effectiveness is hampered by inaccurate collection times, limited manpower, road access constraints, and minimal response to public complaints. The study's conclusions emphasize that improving the effectiveness of waste collection services requires additional manpower, strengthening the monitoring system, improving coordination between relevant parties, and optimizing infrastructure to ensure more consistent and sustainable service delivery.   Keywords: Service Effectiveness, Waste Collection, Bumdesma, Waste Management